A conserved mechanism for stabilization of viral innate immune antagonists via interaction with Elongin BC - Qiru Zeng; Jinyi Sun; Tanner M. Tessier; Gaopeng Hou; Giorgia Piserchia; Longjun Guo; Hong Mei; Matthew D. Weitzman; Siyuan Ding (Proceedings of the National Academy of Sciences, 2026)
Interferon regulator factor 3 (IRF3) inhibition is a shared strategy of many virally encoded proteins to effectively block the induction of interferon signaling. Although rotavirus nonstructural protein 1 (NSP1) is known to target IRF3 for proteasomal degradation, the exact molecular mechanism remains unclear. Here, we found that rotavirus NSP1 contains a BC box motif that mediates interaction with the Elongin BC complex. Either siRNA knockdown or CRISPR knockout of TCEB2 , which encodes Elongin B, substantially prevented IRF3 degradation by NSP1. Recombinant rotaviruses that encode NSP1 with BC box mutations failed to degrade IRF3, induced elevated interferon responses, and were attenuated in interferon-competent cells in vitro and in vivo. NSP1 protein was significantly less stable in infected cells in the absence of Elongin B. Importantly, Elongin BC was required for the stability of additional BC box-containing viral antagonists, including pestiviral N proteases and human adenovirus E4orf6, indicating that Elongin BC functions not only as an adaptor for host protein degradation but also as a broadly exploited stabilizing factor for viral innate immune antagonists. This knowledge of virus co-opting of the host ubiquitin ligase machinery may instruct the development of broad-spectrum antiviral therapeutics.